Predictors of Women's Postpartum Health Status in the First 3 Months After Childbirth - Sukhee Ahn, PhD, RN; JoAnne M. Youngblut, PhD, RN, FAAN (Elsevier, 2007)
The purpose of this study was to examine the significant predictors of postpartum health indicated by physical health, mental health, and role performance during the first 3 months postpartum. Methods: This study used a correlational survey design. The study subjects were 152 mothers at 6 weeks postpartum (T1) and 131 mothers at 3 months postpartum (T2). At 6 weeks and 3 months postpartum, subjects completed a packet of instruments-measuring physical and mental health, role performance, sense of mastery, social support, and infant temperament. Results: Findings indicated that lower family income, more difficult infant temperament, and lower sense of mastery were consistently significant predictors of poorer health outcomes during the postpartum period. Having preterm infants and caring for them was related to higher levels of maternal fatigue in the morning at 6 weeks. Employment did not influence postpartum health. Conclusion: The findings suggest that mother and infant's individual factors and environmental context may continue to negatively affect the mother's health outcomes during the postpartum period.